THE EFFECTS OF OPERATING CASH FLOW DISCLOSURE ON ANALYSTS’ FORECASTS - Mohammed Saadi Kadhim; Hazem Mohammed Daikh; Ghiyath Jasim Saeed (European Journal of Humanities and Educational Advancements, 2022)
Shareholders and creditors pay special attention to companies’ cash flow when investing. Because operating cash flow is one of the most important indicators of company performance, which is an essential tool for assessing debt repayment power and determines the degree of a company’s financial flexibility, on the other hand, it has expected that with the increase in cash flow, it will reveal the opportunistic behaviors of managers and the problems of representation will increase. Analysts’ noses have paid off. The present research has applied in terms of the type of purpose, and its method and nature is descriptive survey. In this study, 139 listed companies of the Tehran Stock Exchange have been selected using the rule of systematic elimination from 2014 to 2018. The study results indicate a significant relationship between earnings forecast error and operating cash flow. And there are positives. There is no meaningful relationship between profit forecast dispersion and operational cash flow. There is also a significant and positive relationship between analyst coverage and operating cash flow.